2020
DOI: 10.1177/1758835920970081
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity and efficacy of shorterversuslonger duration of anthracycline-taxane neoadjuvant chemotherapy in stage II–III HER2-negative breast cancer: a 10-year, retrospective analysis

Abstract: Background: Neoadjuvant anthracycline-taxane-based chemotherapy (ChT) is a standard of care treatment option for stage II–III breast cancer (BC) patients. However, the optimal duration of neoadjuvant ChT has been poorly investigated so far. Material and methods: We retrospectively retrieved clinical data of patients with stage II–III human epidermal growth factor receptor 2-negative (HER2–) BC who were treated between October 2007 and January 2018 with neoadjuvant AT (doxorubicin-paclitaxel) for three cycles f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The results from large randomised clinical trials have shown that neo-adjuvant and adjuvant chemotherapy is associated with similar long-term outcomes [ 5 , 16 , 17 ]. Preoperative chemotherapy has the advantage of being able to induce a reduction in tumour size [ 5 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results from large randomised clinical trials have shown that neo-adjuvant and adjuvant chemotherapy is associated with similar long-term outcomes [ 5 , 16 , 17 ]. Preoperative chemotherapy has the advantage of being able to induce a reduction in tumour size [ 5 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results from large randomised clinical trials have shown that neo-adjuvant and adjuvant chemotherapy is associated with similar long-term outcomes [ 5 , 16 , 17 ]. Preoperative chemotherapy has the advantage of being able to induce a reduction in tumour size [ 5 , 16 ]. Furthermore, the antitumor activity of neoadjuvant chemotherapy can provide valuable prognostic information, as patients achieving a PCR have significantly longer DFS and OS, especially for TN or HER2+ BC [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, regimens that include doxorubicin are listed in The National Comprehensive Cancer Network guidelines as an alternative option in all risk levels and stages of breast cancer except for the lowest risk and early‐stage breast cancer 3 . However, the use of other anticancer agents has led to the study of a greater number of combinations of chemotherapeutic drugs in specific patients, and consequently anthracycline‐based chemotherapy (ABC) has been in decline for decades 8,9 . Additionally, anthracyclines exert remarkable adverse effects and among them, cardiotoxicity is the main one.…”
Section: Introductionmentioning
confidence: 99%